Austria : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper reviews two main issues pertaining to Austrian economy: (1) Austria's long-term fiscal sustainability in light of current tax and expenditure trends, and (2) Austria's macroeconomic challenges and opportunities due to immigration. To maintain fiscal sustainability over the longer run, Austria needs to implement a strategy based on structural expenditure consolidation. Attention to the structure of Austrian taxes and expenditure is germane because this displays important differences vis-a-vis European peers. In 2015, Austria has recorded about 90,000 asylum applicants, making it one of the top three host countries relative to its population. Austria attracts immigrant populations that improve the characteristics of its labor force.